Assessing the consistency of John Calvin’s doctrine on human sinfulness - Nico Vorster (HTS Teologiese Studies/Theological Studies, 2015)
The accusation is often levelled at Calvin that his doctrine on sin is inconsistent, contradictory, deterministic and culpable of making God the Author of sin. This article probes the validity of these accusations by analysing the consistency of John Calvin’s doctrine on human sinfulness and by asking whether Calvin’s understanding of sinful human nature is theologically valid. In doing so, the investigation keeps in mind the structural make-up of his theology, the rhetorical intent of his utterances and the devices he employs to harmonise possible inconsistencies in his theology. The finding is that characterisations of Calvin’s doctrine on sin as deterministic, logically inconsistent and culpable of making God the Author of sin are not well-founded. Factors often overlooked are the dialectical nature of his theological reflection on sin, the chronological evolution of his thought on sin and the fact that he does not regard God and human beings as operating on the same ontological level, though this does not mean that God is not active in creaturely reality. When these factors are taken into account, Calvin’s doctrine on sin proves to be fairly consistent and reconcilable with the rest of his theology.